Общество, среда, компетенция. Еще раз о пользе словарей(Society, Environment, Competence. Once More on the Use of Dictionaries) - Komarova, Olga (Poljarnyj vestnik, 1999)
It is of great help for everybody involved in any type of translating activity to have access to a reliable dictionary. For any language student mastery of the art of using a dictionary is necessary, and many a university lecturer has experienced in his teaching practice that students lack this important skill. What makes things even more difficult is that dictionaries are not always effective in reflecting current developments in the meaning and usage of lexical units. The article illustrates this by demonstrating the difficulties in finding true Russian equivalents to the Norwegian words "samfunn", "miljø" and "kompetanse", using the definitions given in Russian and Russian-Norwegian dictionaries. This leads to a discussion of a different presentation of the semantic characteristics of these lexical units and of their contextual changes of meaning and usage in the two languages.